Effect of sub-lethal High Pressure Homogenization treatments on the functional and biological properties of probiotic bacteria - Tabanelli, G. (2013)
The aim of this work was to assess if a sub-lethal high pressure homogenization (HPH) treatment could modulate in vitro functional and biological properties of probiotic bacteria. Lactobacillus paracasei A13, Lactobacillus acidophilus 08 and Dru, Lactobacillus delbrueckii subsp. lactis 200 and bile-resistant derivatives L. acidophilus Druþ and L. delbrueckii subsp. lactis 200þ were suspended in phosphate buffered saline solution and treated at 50 MPa. Data obtained showed that HPH can modulate hydrophobicity and auto-aggregation without modification of viability and decarboxylase activity. Resistance to simulated gastric conditions resulted strain-dependent. High resistance was observed for treated L. paracasei A13, L. acidophilus Dru and 08 and L. delbrueckii subsp. lactis 200. The HPH-treatment reduced the resistance to simulated stomach duodenum-passage of L. acidophilus Dru while increased it for L. paracasei A13. Strain viability and resistance to simulated gastric conditions were evaluated treating at 50 MPa cells suspended in acidified buttermilk (pH 4.6) and stored at 4 C for 30 days. The highest cell viability loss, after 30 d of refrigerated storage, was observed for L. acidophilus Dru, independently of the application of HPH. However, after 30 days of storage, the resistance of L. paracasei A13 to simulated gastric digestion significantly increased in HPH treated cells.